2018
DOI: 10.1021/acs.jafc.8b02992
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Inhibition Mechanism of Betulinic Acid on α-Glucosidase

Abstract: Betulinic acid (BA), an important pentacyclic triterpene widely distributed in many foods, possesses high antidiabetic activity. In this study, BA was found to exhibit stronger inhibition of α-glucosidase than acarbose with an IC value of (1.06 ± 0.02) × 10 mol L in a mixed-type manner. BA bound with α-glucosidase to form a BA-α-glucosidase complex, resulting in a more compact structure of the enzyme. The obtained concentrations and spectra profiles of the components resolved by the multivariate-curve resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 148 publications
(79 citation statements)
references
References 53 publications
(103 reference statements)
12
66
1
Order By: Relevance
“…The values of K a and n at 298, 304, and 310 K were calculated with Eqn 6 (Table ). K a is the binding constant for the α ‐glucosidase–CRA complex, the order of magnitude of the K a values was 10 3 L mol −1 , indicating a moderate binding affinity in the binding reaction of CRA with α ‐glucosidase, which was consistent with the binding of betulinic acid to α ‐glucosidase determined by Ding et al . Recent studies by Zhang et al .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The values of K a and n at 298, 304, and 310 K were calculated with Eqn 6 (Table ). K a is the binding constant for the α ‐glucosidase–CRA complex, the order of magnitude of the K a values was 10 3 L mol −1 , indicating a moderate binding affinity in the binding reaction of CRA with α ‐glucosidase, which was consistent with the binding of betulinic acid to α ‐glucosidase determined by Ding et al . Recent studies by Zhang et al .…”
Section: Resultssupporting
confidence: 81%
“…The values of K a and n at 298, 304, and 310 K were calculated with Eqn 6 ( Table 2). K a is the binding constant for the -glucosidase-CRA complex, the order of magnitude of the K a values was 10 3 L mol −1 , indicating a moderate binding affinity in the binding reaction of CRA with -glucosidase, 18 which was consistent with the binding of betulinic acid to -glucosidase determined by Ding et al 44 Recent studies by Zhang et al had found that CRA had a high absorption rate in the stomach of rat and showed a good permeability in the intestine. Its effective permeability in the ileum at 9 μg/mL (1.91 × 10 −5 mol L −1 ) was remarkably higher than the IC 50 value of CRA on -glucosidase.…”
Section: Thermodynamic Parameterssupporting
confidence: 83%
“…It was difficult to distinguish the spectra of 5‐HMF–ctDNA complex and judge whether the interaction between 5‐HMF and ctDNA occurred. Hence, the MCR‐ALS method was introduced to resolve the complex spectral data matrix to obtain detailed information of the 5‐HMF–ctDNA interaction …”
Section: Resultsmentioning
confidence: 99%
“…The CD spectra of SPI had one negative band at 216 nm due to the existence of β-sheet (Figure 2c; Ding et al, 2018). With increasing concentrations of TG (from 0 to 8.0 U/g) to SPI solution, a gradual lessening in the intensity of the negative band was observed, the contents of the α-helix and β-sheet decreased from 5.32% to 3.42% and 49.53% to 44.91%, respectively, whereas the contents of random and coil β-turn increased from 23.89% to 28.94% and 21.87%…”
Section: Secondary Structuresmentioning
confidence: 99%